2023
DOI: 10.1021/acsnano.3c01298
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Electrolytes in the Relaxation of Near-Surface Spin Defects in Diamond

Abstract: Quantum sensing with spin defects in diamond, such as the nitrogen vacancy (NV) center, enables the detection of various chemical species on the nanoscale. Molecules or ions with unpaired electronic spins are typically probed by their influence on the NV center’s spin relaxation. Whereas it is well-known that paramagnetic ions reduce the NV center’s relaxation time (T 1), here we report on the opposite effect for diamagnetic ions. We demonstrate that millimolar concentrations of aqueous diamagnetic electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Since the excitation power intensity (9 kW cm −2 ) used is below saturation (~100 kW cm −2 ) 48 and surface oxygenation stabilizes shallow negatively charged NVs 49 , effects attributed to NVs charge conversion are neglected in this work. Moreover, concentration of 10 mM of diamagnetic NaCl used in the presented measurements has been shown not to affect T 1 46 . Furthermore, we test if charged miR-21 adsorbates induce observable electric noise by measuring the change in spin relaxation contrast with no Mn ions present (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Since the excitation power intensity (9 kW cm −2 ) used is below saturation (~100 kW cm −2 ) 48 and surface oxygenation stabilizes shallow negatively charged NVs 49 , effects attributed to NVs charge conversion are neglected in this work. Moreover, concentration of 10 mM of diamagnetic NaCl used in the presented measurements has been shown not to affect T 1 46 . Furthermore, we test if charged miR-21 adsorbates induce observable electric noise by measuring the change in spin relaxation contrast with no Mn ions present (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 72%
“…It has been shown that spin relaxation measurements, apart from temperature, can also be susceptible to NV centers charge conversion (induced by laser excitation) 45 , diamagnetic electrolyte solutions 46 and electric noise 29 , 47 . Since the excitation power intensity (9 kW cm −2 ) used is below saturation (~100 kW cm −2 ) 48 and surface oxygenation stabilizes shallow negatively charged NVs 49 , effects attributed to NVs charge conversion are neglected in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Adding to the results in Figure 1d , the solid circles and lines in Figure 3c respectively show the relative SiV − fluorescence as a function of time for λ IR = 750 nm and the calculated fits using Equation 3 assuming r 0 = 1 nm, as seen for NV centers; [ 36 ] in all cases, we set the nitrogen concentration at 3 ppm, consistent with prior observations in this same sample crystal. [ 22 ] Comparison between the measured and calculated SiV response shows good agreement (see also Section S2 , Supporting Information for the complete data set).…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that a diamagnetic electrolyte near the NV center reduces both electric and magnetic noise, consequently improving T 1 . A theoretical calculation for the T 1 relaxation time of an NV center proximate to a 2D spin liquid shows similar effects of a diamagnetic state on the T 1 .…”
mentioning
confidence: 96%